Factors Affecting Customer Satisfaction on Automated Teller Machines Provided by Commercial Banks in Kathmandu Valley - Dongol, Padam; Shukla, Shilpa (Campion Journal of Multidisciplinary Research and Explorer, 2025)
This study investigates the factors influencing customer satisfaction with Automated Teller Machines (ATMs) provided by commercial banks in Kathmandu Valley. ATMs are pivotal in modern banking, offering 24/7 access to financial services, including cash withdrawals, balance inquiries, and bill payments. The research examines key factors such as security and privacy, convenience, system availability, speed of ATM services, responsiveness, and reliability. Primary data was collected from 100 ATM cardholders across five major commercial banks through a structured questionnaire. The study employs both descriptive and inferential statistical methods, including regression analysis, to assess the impact of these variables on customer satisfaction. Results indicate that convenience and system availability significantly influence customer satisfaction, while security and privacy, speed, responsiveness, and reliability show less impact. The findings highlight the importance of improving ATM service quality to enhance customer satisfaction and provide a competitive edge in the banking sector. The study also contributes to the literature by focusing on factors such as system availability and security that have been underexplored in previous research.